2005
DOI: 10.1103/physrevlett.95.217206
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Exchange Interactions in Quantum Dots Containing Electrons and Magnetic Ions

Abstract: We present a theory of magnetic exchange interactions in quantum dots containing electrons and magnetic ions. We find the interaction between the electron and Mn ion to depend strongly on the number of electrons. It can be switched off for closed shell configurations and maximized for partially filled shells. However, unlike the total electron spin S which is maximized for half-filled shells, we predict the exchange interaction to be independent of the filling of the electronic shell. We show how this unusual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
109
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 20 publications
3
109
1
Order By: Relevance
“…From the theory side there is a lot of interest on the effect of number of carriers on the magnetic properties of a dot doped with Mn atoms. 9,11,16,25,[37][38][39] A priori, the ground state of a negatively charged InAs dot doped with a single Mn should be the ionized A − acceptor, with spin properties identical to those of Mn in neutral CdTe. 14 Band-to-band transitions should yield zero-field PL spectra with 6 peaks.…”
Section: Charged Exciton Spectroscopymentioning
confidence: 99%
“…From the theory side there is a lot of interest on the effect of number of carriers on the magnetic properties of a dot doped with Mn atoms. 9,11,16,25,[37][38][39] A priori, the ground state of a negatively charged InAs dot doped with a single Mn should be the ionized A − acceptor, with spin properties identical to those of Mn in neutral CdTe. 14 Band-to-band transitions should yield zero-field PL spectra with 6 peaks.…”
Section: Charged Exciton Spectroscopymentioning
confidence: 99%
“…Unlike in the bulk structures, adding a single carrier in a magnetic QD can have important ramifications. An extra carrier can both strongly change the total carrier spin and the temperature of the onset of magnetization which we show can be further controlled by modifying the quantum confinement and the strength of Coulomb interactions.We study the magnetic ordering of carrier spin and magnetic impurities in (II,Mn)VI QDs identified as a versatile system to demonstrate interplay of quantum confinement and magnetism [4,5,6,15,16,17,18]. Because Mn is isoelectronic with group-II elements it does not change the number of carriers which in QDs are controlled by either chemical doping or by external electrostatic potential applied to the metallic gates.…”
mentioning
confidence: 99%
“…By using real space finite-temperature local spin density approximation (LSDA) [19] we study temperature (T ) evolution of magnetic properties of QDs over a large parameter space. This approach allow us to consider QDs with varying number of interacting electrons (N ) and Mn impurities (N m ) which already for small N and N m becomes computationally inaccessible to the exact diagonalization techniques [18,20]. We extend the previous studies of Coulomb interactions in magnetic QDs with N m = 1, 2 at T = 0 [18] and T > 0 results using either Thomas-Fermi approximation or by applying Hund's rule with up to 6 carriers [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a CdTe semiconductor QD, the corresponding Zeeman splitting of an electron reaches |g * µ B B| = 0.64meV , where the g-factor is given by g * = −1.67 in this material. 36 To guarantee the left QD and the right lead is not effectively influenced by the surrounding magnetic field, magnetic shielding may be applied here to protect the spreading field. One kind of the magnetic shielding materials is superconducting chip which expels magnetic field via the Meissner effect.…”
Section: Discussionmentioning
confidence: 99%